"Yakety yak: Don't talk back": An autopsy of anonymity gone awry. Issue 1 (3rd April 2022) - Montalbano, Kathryn
Abstract: This article compares the socio-legal factors and challenges contributing to the failure of the deceased anonymous, hyperlocal platform, Yik Yak, with a living anonymous, hyperlocal platform, Jodel. By analysing each platform's Terms of Service (ToS) statements alongside their guidelines and values, the article traces how anonymous, hyperlocal applications both diverge from and mirror communication law in fashioning their approaches to content moderation and responses to the dark side of communication. The article concludes that in contrast with Yik Yak, which attempted to rely on its ToS and limited community monitoring system to curb cyberbullying and harassment, the case of Jodel—and by extension, the German approach to regulating hate speech and bullying—suggests that surviving hyperlocal, anonymous platforms of U.S. origin should not solely hide behind Section 230 of the Communications Decency Act (CDA). Instead, they should aim to combine (1) robust ToS statements with (2) specific community values or guidelines that are fortified by (3) a comprehensive monitoring system in order to curb abusive behaviour on their platforms.